Mismanagement Reasons of the Projects Execution Phase (Journal of Engineering, 2017)
The execution phase  of the project is most dangerous and the most drain on the resources during project life cycle, therefore, its need to monitor and control by specialists to exceeded obstructions and achieve the project goals. The study aims to detect the actual reasons behind mismanagement of the execution phase. The study begins with theoretical part, where it deals with the concepts of project, project selection, project management, and project processes. Field part consists of three techniques: 1- brainstorming, 2- open interviews with experts and 3- designed questionnaire (with 49 reason. These reasons result from brainstorming and interviewing with experts.), in order to find the real reasons behind mismanagement of the execution phase. The most important reasons which are negatively impact on management of the execution phase that proven by the study were (Inability of company to meet project requirements because it's specialized and / or large project, Multiple sources of decision and overlap in powers, Inadequate planning, Inaccurate estimation of cost, Delayed cash flows by owners, Poor performance of project manager, inefficient decision making process, and the Negative impact of people in the project area). Finally, submitting a set of recommendations which will contribute to overcome the obstructions of successful management of the execution phase.